The Antecedents to Consumers’ Attitude Towards Mobile Advertising COVID-19 Communications: A Post-pandemic South African Perspective - Masocha, Reginald (AFEBI Management and Business Review, 2024)
The Covid-19 pandemic, although officially declared over, continues to influence global communication behaviors. In this context, mobile communication devices have become essential tools for both business and non-business communicators. This study investigates the antecedents shaping consumers’ attitudes towards Covid-19-related communications delivered via mobile advertising in South Africa. Using a quantitative approach, data were collected through an online survey with purposive sampling, and hypotheses were tested using one-way ANOVA. The findings reveal that despite the widespread ownership and use of mobile devices and the severity of Covid-19, consumers do not automatically engage with mobile communications. Key factors influencing attitudes include message credibility, perceived relevance, and emotional appeal. The study highlights the need for communicators to strategically consider these elements to enhance message effectiveness. By identifying critical antecedents to mobile communication acceptance in a post-pandemic environment, this research contributes to the broader understanding of consumer behavior in mobile advertising and offers practical implications for designing more effective health and commercial communication strategies. Keywords: Covid 19, Consumer Attitude, Communications, Antecedents.